High-efficiency pervaporative separation of fuel bioadditive methylal from methanol by poly(vinyl alcohol)/poly(vinylpyrrolidone) blend membrane - Unlu, Derya (Springer Heidelberg, 2023)
Methylal is a fuel bioadditive. The purification of methylal has been conducted by the pervaporation process. The purification of methylal from the reaction mixture is required to use the methylal as a fuel additive for diesel or biodiesel. In this study, poly(vinyl alcohol) (PVA) and poly(vinylpyrrolidone) (PVP) polymers were used and the blend membrane was prepared by using these polymers. The prepared PVA/PVP blend membranes have been utilized for the separation of methylal/methanol binary mixtures and methylal/methanol/water ternary mixtures in a pervaporation process. Membranes were characterized by Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Thermogravimetric analysis (TGA), contact angle measurements and X-ray Diffraction Analysis (XRD). Pervaporation tests were performed at different feed concentrations, operation temperatures and PVP loading ratios. The best separation performance was obtained at 10 wt. % of PVP loaded membrane. Optimum process conditions were determined as 30 degrees C of operation temperature and 5 wt. % of feed methanol concentration. Under these conditions, methanol flux and methanol selectivity values were 0.21 kg/m(2) h and 98.01, respectively. Approximately, 99% of purity methylal has been achieved in the retentate stream by removing the methanol. The innovation of this study is to develop an alternative method, which is of high purity and low energy consumption according to the literature, for the purification of methylal biofuels.
Keywords: Fuel bioadditive; Membrane; Methanol; Methylal; Pervaporation; Separation